Prolidase expression in knee osteoarthritis and healthy controls: Observational study. Issue 35 (3rd September 2021) - Silva-Luna, Karina; Ventura-Ríos, Lucio; López-Macay, Ambar
Abstract : Abstract: Prolidase enzyme activity is important for collagen resynthesis. In late stages of osteoarthritis (OA) its activity is decreased. To evaluate prolidase expression in knees of patients undergoing total arthroplasty for OA, and compare with young people undergoing knee arthroscopy due to traumatic injuries. In this cross-sectional study we included 20 patients with OA grade IV who underwent total knee arthroplasty and 20 controls of young patients who underwent arthroscopy for another reason besides OA. All participants were evaluated by knee ultrasound before the procedure. During the procedure, synovial tissue biopsies were taken and analyzed by immunofluorescence to search inflammation. Measures of central tendency, dispersion measures and position measures were used for the case of quantitative variables. Student t test or Mann–Whitney U test, and the logistic regression of Cox, was used. Prolidase expression in the synovial biopsy was significantly lower in the OA group than in the controls (0.017 ± 0.009 vs 0.062 ± 0.094, P  < .05). Power Doppler (PD) signal was present in the synovitis of all knee recesses of the OA group in grayscale and in 17 (85%) of knees. The mean of the micro-vessel count in patients with OA was significantly higher vs controls (11 + 5.3 vs 4 + 2.1, P  = .001). The neovascularization correlated significantly with the presence of PD signal in patients with OA (1.16, 95% CI, 1.02–1.34, P  = .02). The prolidase expression in the synovial membrane evaluated by immunofluorescence, in patients with late stages of knee OA, is low, which may be interpreted as an evidence of decreased collagen resynthesis. Abstract : Supplemental Digital Content is available in the text